Comparison of prophylactic percutaneous endoscopic gastrostomy with reactive enteral nutrition in patients with head and neck cancer undergoing radiotherapy or chemoradiotherapy: A systematic review. (December 2021) - Mellors, Kate; Ye, Xiaodan; Van Den Brande, Jonathan; Wai Ray Mak, Tsz; Brown, Teresa; Findlay, Merran; Bauer, Judy
Summary: Background & aims: Nutrition support is frequently indicated in patients with head and neck cancer (HNC). However, the optimal timing of enteral tube placement and feeding commencement is unknown. This review aims to compare the outcomes for patients with HNC undergoing curative intent radiotherapy (RT) or chemoradiotherapy (CRT) receiving either prophylactic percutaneous endoscopic gastrostomy (pPEG) tube placement/feeding or reactive enteral nutrition (rEN). Methods: A literature search was conducted in March 2020 across PubMed, CINAHL, Embase, Web of Science, and Scopus. Randomized controlled trials (RCTs) of patients (≥18 years) with HNC who had received either pPEG or rEN were included. Outcomes examined were weight change, nutritional status, body mass index, treatment interruptions, quality of life (QoL), disease-free survival and overall survival. Study quality and certainty of evidence were assessed using the Cochrane Risk-of-bias Tool for Randomized Trials Version 2 and the Grading of Recommendations Assessment, Development and Evaluation system, respectively. Results: Five studies (three RCTs) (n = 298) were included and definitions of pPEG and rEN were heterogenous. pPEG was associated with a clinically important reduction in short-term critical weight loss (>10% weight loss), and significantly improved short-term QoL in patients with HNC. The timing of nutrition support commencement had no effect on all other outcomes. The overall certainty of evidence was 'moderate' for: nutritional status; treatment interruptions; short-term QoL; disease-free survival; and 'low' for all other outcomes. Conclusions: Patients with HNC undergoing RT or CRT receiving pPEG tube feeding/placement were less likely to experience short-term critical weight loss and have improved short-term QoL compared to rEN. Further well-designed RCTs with consistent definitions of tube feeding protocols and the use of validated tools to evaluate nutritional status, will assist to increase the certainty of evidence and confirm the beneficial effects observed.